AVIATION PROFESSIONALS SELF-DEVELOPMENT AS A COMPONENT OF PROFESSIONAL TRAINING - Смірнова, І. Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is devoted to the problem of the need for the formation of professional self-development of future aviation specialists during training and the problems that are associated with it. The author has identified the components of professional self-development and methods by which this goal may be achieved during theoretical training in flight educational establishments. The author reviewed the challenges concerning this problem in professional pedagogy during teaching of professional subjects in flight educational establishments